3X-2(-5X-3)=-72
3x+10x+6=-72
13x+6=-72
13x=-78
x=-6
now solve for y
-5(-6)-3=y
y=27
now check your answers
3(-6)-2(27)=-72
-18-54=-72
so
y=27 and x=-6
2006-12-07 18:23:15
·
answer #1
·
answered by ken 2
·
0⤊
0⤋
y = -5x - 3
3x - 2y = -72
In order to solve using the substitution method, solve one variable in terms of the other and then plug into the second equation.
In this case, we're lucky, because y = -5x - 3 is already solved in terms of x. Now, we just plug y = -5x - 3 into the second equation
3x - 2y = -72
3x - 2[-5x - 3] = -72
3x + 10x + 6 = -72
13x = -78
x = -6
To solve for y, all we have to do is plug in x = -6 to any of those two equations. Let's use the first one.
y = -5x - 3
y = -5(-6) - 3
y = 30 - 3
y = 27
Therefore, x = -6 and y = 27
2006-12-08 02:18:29
·
answer #2
·
answered by Puggy 7
·
0⤊
0⤋
well, you want to pick one equation, and substitute out the x or
y in it, for the y= or x= equivalent form of the other equation.
Since the first equation already says "y=" heck just substitute
that into the y in the 2nd equation. Then you've got an equation
with just x's and numbers. Solve for x by adding/subtracting/multiplying/dividing..
once you have x= a number, substiute that number for
the x in either of the
original equations, and do the same thing to figure out y.
basically x and y are just two values that are constrained
to be related somehow, by the first equation. If I tell you
another way they're related, which is the 2nd equation,
then I can figure out what the two values are...If I didn't
tell you the 2nd equation, then x and y could be lots of values.
But with the 2nd equation, there's only one answer that
works for both equations.
2006-12-08 02:22:50
·
answer #3
·
answered by Johnny R 1
·
0⤊
0⤋
y= -5x - 3 --------- (1)
3x - 2y = - 72 ---- (2)
substitute (1) into (2),
3x - 2(-5x - 3) = -72
3x + 10x + 6= -72
13x = -78
x = -6
substitute (x= -6) into (1)
y= -5(-6) - 3
y= 30 - 3
y= 27
hence, y= 27 and x =6
2006-12-08 02:22:04
·
answer #4
·
answered by KeSin 1
·
0⤊
0⤋
3x - 2y = -72 but y = -5x -3
therefore
3x - 2(-5x -3) = -72
3x + 10x + 6 = -72
13x = -78
------>x = -6
sub x into 1st equation
3(-6) - 2y = -72
----->y = 27
2006-12-08 02:17:15
·
answer #5
·
answered by brock_wht 1
·
0⤊
0⤋
yay!! math :)
okay...!
y is already solved for, this means that it equals -5x-3.
--> (Y= -5X - 3)
Sooo...
plug in what y equals in the other equation...
-->3X - 2Y= -72
goes to
---->3X - 2(-5X - 3)= -72
solve for x
multiply through
---> 3X + (- 2)(-5X) + (-2)(-3)= -72
add like terms
---> 3X + 10X + 6= -72
---> 13X + 6 = - 72
subtract five on each side
---->13X=-78
multiply by (1/13) on each side
---> X= -78/13
---> X = -6
Then, solve for y: (Y= -5X - 3)
plug in the x value
y = -5(-6) -3
y = 30 - 3
y = 27
and your ordered pair is (-6, 27)
2006-12-08 02:23:30
·
answer #6
·
answered by rainfairy 2
·
0⤊
0⤋
3x - 2(-5x-3) = -72
3x + 10x + 6 = -72
13x = -78
x = -6
y = -5(-6) -3
y = 30 - 3
y = 27
2006-12-08 02:17:53
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
3X-2(-5X-3)= -72
3X+10X+6=-72
13X+6=-72
13X=-78
X=-78/13
X=-6
2006-12-08 02:17:19
·
answer #8
·
answered by coffiegrl 1
·
0⤊
0⤋